# How do you write the nth term of the arithmetic sequence -26, -15, -4, 7,...?

##### 1 Answer

Mar 5, 2017

#### Explanation:

The way to get any equation off an arithmetic sequence is using this:

# t(n) = a + (n - 1)(d) # d = the difference between two terms

n = term number

a = 1st term

As we can see from the sequence:

a = -26

d = 11

Substitute:

#-> t(n) = -26 + ( n - 1 )( 11 ) #

#-> t(n) = 11n - 37 #

P.S.

I'm not sure whether you want this type of nth term equation or the recursive one.